Performance profile analysis of ZnO/CdS/CdTe solar cells thin film : A review of absorber thickness and device temperature. (June 2020) - Putra, N M D; Sugianto,; Marwoto, P; Murtafiatin, R; Rizaldi, P D
Abstract: ZnO/CdS/CdTe solar cell performance modeling has been done using AFORS-HET. The performance of solar cells is assessed based on the thickness of the CdTe absorber and device temperature. The thickness of CdTe varies from 100 nm - 5 μm and the temperature of the device is varied from 295 K, 300 K and 305 K. The characteristic I-V results show that samples with higher CdTe thickness have greater performance efficiencies. Conversely, the temperature variation of the device shows that the higher temperature of the device, the performance of solar cell efficiency will decrease. The optimum performance of ZnO/CdS/CdTe solar cells is owned by solar cells with a thickness of 4, 500 nm CdTe absorber with VOC, JSC, FF, and efficiency values at 300 K device temperature respectively for 967 mV; 27.6 mA / cm2; 86.95%; and 23.21%.